Impact of Russia-Ukraine Conflict on Turkey's Economic Stability - Salma Salsabila; Mohammad Izdiyan Muttaqin (Ridwan Institute, 2023)
The conflict between Russia and Ukraine has significant implications for the stability of global order. Turkey, as a country that has profound relations with Russia and Ukraine, is also affected by the conflict that threatens the country's economic sector, which is currently in reform momentum. The Turkish government under President Recep Tayyip Erdogan strategically seeks to position itself as a conflict mediator to reach a peace resolution that will ultimately have an impact on the restoration of productive relations with Russia and Ukraine. The author will use a qualitative research approach with analytical descriptive methods that utilize various sources such as journals, books, scientific articles, media and other sources that have gone through the study process. This study uses the theory of national interest and rational choice to observe and identify President Erdogan's decision-making process in responding to the Russian-Ukrainian conflict in a constructive and balanced manner without showing dominant partiality to either party. The results showed that the conflict between Russia and Ukraine had a significant impact on the stability of the Turkish economy, which strategically responded through restorative-based policies to rejuvenate productive relations with the two countries in conflict.